Analysis of rice supply chain mechanism with simulation approach - B N Alfa; Subagyo Subagyo (IPTEK Journal of Proceedings Series, 2018)
Rice is the staple food consumed by most of Indonesian population, which is about 89.22 kg/capita/year during 2007-2014 with consumption percentage of 85.88%-91.73% during the year. Rice issues are a strategic issue given that food sovereignty is one of the government's strategic plans. The supply chain of rice is a complex system involving many interacting variables. Rice production exceeds its consumption, causing Indonesia to become a surplus country. Despite Indonesia's rice surplus, the government is still engaged in rice imports to ensure the availability of rice in some deficit provinces. This research aims to develop national rice supply chain model and distribution mechanism model between surplus and deficit province. The complexity of the mechanism and behavior of the system is considered in the selection of research methods using system dynamics simulation to solve the problem. The mechanism applies the principle of the transfer process in which displacement will occur if there are differences in conditions in the two adjacent materials. The result of the research shows that the built model has a MAPE value of 1.58% for wetland variables, 3.81% for rice production variables, 2.57% for population variables and 3% for rice distribution variables, with evaluation of each province availability is above zero.